Diet composition of Dasyatis marianae (Elasmobranchii: Dasyatidae) off Paraíba State, Brazil - Shibuya, Akemi (2011)
Dasyatis marianae is a costal stingray that lives associated with coral and sandstone reefs. This species has been captured in the artisanal fishery along Paraíba State’s coast, Brazil. Its diet was studied through stomach contents analysis of individuals captured with hand line off Conde county. The prey items were identified to the lowest possible taxonomic level or category. The results indicated that the diet is dominated by crustaceans and revealed seven prey groups: Penaeidae, Caridea, Callinectes exasperatus, Epialtus sp., Acanthonyx sp., Amphipoda and Isopoda. Annelida, Mollusca and Teleostei also occurred with minor participation. The Index of Relative Importance indicated that the shrimp group (67.75%) and crab group (29.16%) were the most important prey items. The stomach contents suggest that D. marianae is a selective feeder on the most abundant prey of its habitat.